Molecular characteristics of eae-positive clinical Shiga toxin-producing Escherichia coli in Sweden - Ying Hua; Xiangning Bai; Ji Zhang; Cecilia Jernberg; Milan Chromek; Sverker Hansson; Anne Frykman; Xi Yang; Yanwen Xiong; Chengsong Wan; Andreas Matussek (Emerging Microbes and Infections)
Shiga toxin (Stx)-producing Escherichia coli (STEC) can cause a wide range of symptoms from asymptomatic carriage, mild diarrhea to bloody diarrhea (BD) and hemolytic uremic syndrome (HUS). Intimin, encoded by the eae gene, also plays a critical role in STEC pathogenesis. Herein, we investigated the prevalence and genetic diversity of eae among clinical STEC isolates from patients with diarrhea, BD, HUS as well as from asymptomatic STEC-positive individuals in Sweden with whole-genome sequencing. We found that 173 out of 239 (72.4%) of clinical STEC strains were eae positive. Six eae subtypes (ϵ1, γ1, β3, θ, ζ and ρ) were identified eae and its subtype γ1 were significantly overrepresented in O157:H7 strains isolated from BD and HUS patients. ϵ1 was associated with O121:H19 and O103:H2 strains, and β3 to O26:H11 strains. The combination of eae subtype γ1 and stx subtype (stx2 or stx1+stx2) is more likely to cause severe disease, suggesting the possibility of using eae genotypes in risk assessment of STEC infection. In summary, this study demonstrated a high prevalence of eae in clinical STEC strains and considerable genetic diversity of eae in STEC strains in Sweden from 1994 through 2018, and revealed association between eae subtypes and disease severity.